2015
DOI: 10.1371/journal.pone.0144263
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Timing of Signal Detection of Adverse Drug Reactions

Abstract: We investigated factors affecting the timing of signal detection by comparing variations in reporting time of known and unknown ADRs after initial drug release in the USA. Data on adverse event reactions (AERs) submitted to U.S. FDA was used. Six ADRs associated with 6 drugs (rosuvastatin, aripiprazole, teriparatide, telithromycin, exenatide, varenicline) were investigated: Changes in the proportional reporting ratio, reporting odds ratio, and information component as indexes of signal detection were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Mass, charge, and pI value of peptide were calculated using R package “ peptides ” ( Osorio et al, 2015 ), which is specifically designed for the quick and easy calculation of different AMPs features. This would help in their better classification and design.…”
Section: Methodsmentioning
confidence: 99%
“…Mass, charge, and pI value of peptide were calculated using R package “ peptides ” ( Osorio et al, 2015 ), which is specifically designed for the quick and easy calculation of different AMPs features. This would help in their better classification and design.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, this study attempted to analyse if the ADR reporting forms contain essential elements to apply causality assessment. .If ADR form includes comments on whether the ADR is known or unknown, it will help faster processing and reduce the signal generation time (Hashiguchi et al 2015). As per this study, it is observed that the forms don't have this entry.…”
Section: Discussionmentioning
confidence: 81%
“…We detected the signals when the ROR estimated and lower limits of the corresponding 95% confidence interval (CI) were greater than 1, and at least 2 cases were required to define the signal [5, 6]. …”
Section: Methodsmentioning
confidence: 99%